PERANCANGAN DAN PEMBUATAN MEDIA PEMBELAJARAN INOVATIF BERBASIS IPTEK BAGI GURU SD PERAIRAN DI KECAMATAN PULAU RIMAU - Sutrisno, Sutrisno (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The objectives of this community partnership (PKM) program are; a) To form Teacher Working Group (KKG); b) to improve teachers knowledge and skill about making instructional media with applied science and technology approach; c) to train the making of instructional media with applied science and technology approach; d) to train and assist the use of instructional media in the classroom. The method of adopting the action research implementation includes four stages: program planning, program implementation, observation and evaluation, and reflection. The results of program implementation are; a) 7 teacher working groups with 4 to 9 members formed based on the location of the area; b) the increased knowledge and skills of teachers on the making of instructional media with applied science and technology approach, from the enough to the good category; c) generated media (props) for elementary students; d) teachers ability to use instructional media in goodquality category.